Application of plant tissue culture in oil palm (Elaeis guineensis Jacq.) for yield improvement- a review / Fatin Nadiah Jamil - Jamil, Fatin Nadiah (Faculty of Plantation and Agrotechnology, 2016)
High yield production of oil palm is vital especially in the economic perspective because its main products i.e., fresh fruit bunch (FFB) and oil yield used as the main sources of natural palm oil production that is fundamental raw material in many industries. With increasing global demands for vegetable oils, the yield productivity must be improved urgently. Through biotechnology, conventional breeding can be supersede by using several micro propagation techniques such as callogenesis, organogenesis and somatic embryogenesis. Several approaches were done vegetatively similar with application of plant tissue culture in oil palm which possible to produce high mass of superior genotype oil palm which genetically uniform planting material with good characteristics, known as an elite clonal oil palm. Malaysia has successfully produce clonal Elaeis guineensis with 2.53 million ramets in 2009. However, the capacity is still not reach the point of high global demand and our country has developed about 12 tissue culture laboratories to improve high production of Elaeis guineensis elite clone. An elite clonal palm would resulting in uniform high yield production which it can be feasibly management of harvesting. The objectives of this review are to identify the best plant tissue culture protocol that gives the optimum success rate of clonal elite planting material of oil palm and to prove that clonal palm as planting material could help for yield improvement. Through this review, several finding could be point out such the issues of ortet availability and flower abnormality of clonal palm.